Gefragte Felle. Biber als Transaktionswährung in der Kolonie New Netherland (1609–1664) - Brugger, Eva (Historische Anthropologie, 2017)
Abstract: „This paper considers beaver fur traded by the Dutch in the 17th century as a global object and transaction currency. The analysis of the fur’s material texture helps to understand how beaver fur could be traded across continental, national, colonial and cultural borders. Beaver fur differed from other Early Modern global objects like cotton, silk, chocolate or porcelain because the skins were used as commodities, resource, dress and currency alike. Beaver furs became global objects because the animal and its habits were known globally even though beaver fur was not globally available in the same quantity and quality. Yet beaver furs were valuable to all participants in the market: native hunters, middlemen, traders, company soldiers and hatters were involved in a global trade fueled by scarcity and longing for fur in Europe.“
Keywords: Albany, NY; Biber; Fell; Handel; Hudson-River-Tal; Indigenes Volk; Kolonialismus; Kulturkontakt; Neuniederlande; New York, NY; Nordamerika; OA/Volltext

Immaterielles Kulturerbe im Museum. Aktuelle Entwicklungen in den Niederlanden - Elpers, Sophie (Schweizerisches Archiv für Volkskunde, 2017)
Keywords: Immaterielles Kulturerbe; Museum; OA/Volltext

Musik als Mittel der Konfessionalisierung in den Niederlanden 1850–1948 - Langen, Petra van (Schweizerische Zeitschrift für Religions- und Kulturgeschichte, 2017)
Keywords: Katholizismus; Kirchenlied; Kirchenmusik; Konfessionalisierung; Musik; Musikleben; OA/Volltext; Protestantismus

Nach 40 Jahren. Erneuerung der deutsch-niederländischen Städtefreundschaft zwischen Rheda-Wiedenbrück und Oldenzaal - Sudhölter, Jürgen (nachbarsprache niederländisch, 2017)
Keywords: OA/Volltext; Oldenzaal; Rheda-Wiedenbrück; Städtepartnerschaft